1996
DOI: 10.1152/ajprenal.1996.270.6.f1027
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate regulation of renal expression of nitric oxide synthase, renin, and angiotensinogen mRNA by dietary salt

Abstract: Experiments were performed to examine the effect of changes in dietary salt intake on the neuronal form of the constitutive nitric oxide synthase (ncNOS, type I NOS), renin, and angiotensinogen mRNA expression in the kidney. Three groups of Sprague-Dawley rats were studied as follows: rats maintained on a 3% Na diet plus 0.45% NaCl in the drinking fluid for 7 days (high salt), rats given a single injection of furosemide (2 mg/kg i.p.) and a 0.03% Na diet for 7 days (low salt), and rats on a diet containing 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
108
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 0 publications
9
108
3
Order By: Relevance
“…The HS diet suppressed PRA in both strains, and PRA was significantly lower in the DSϩLS group compared with the DRϩLS group, as previously shown. 4 The HS diet has been shown to suppress plasma and intrarenal expression of AGT in Sprague-Dawley 16,17 and Wistar-Kyoto 18 rats. Similarly, in the present study, plasma Ang II and AGT levels were also suppressed by HS diet in both DR and DS strains.…”
Section: Discussionmentioning
confidence: 99%
“…The HS diet suppressed PRA in both strains, and PRA was significantly lower in the DSϩLS group compared with the DRϩLS group, as previously shown. 4 The HS diet has been shown to suppress plasma and intrarenal expression of AGT in Sprague-Dawley 16,17 and Wistar-Kyoto 18 rats. Similarly, in the present study, plasma Ang II and AGT levels were also suppressed by HS diet in both DR and DS strains.…”
Section: Discussionmentioning
confidence: 99%
“…Results regarding the distal [NaCl] and the production of NO in MD in earlier studies are somewhat conflicting. In studies concerning the influence of sodium intake on NOS expression, it has been found that sodium deficiency stimulates nNOS expression, as do other conditions that are likely to result in reduced MD [NaCl] or transport, such as furosemide administration and unilateral stenosis of the renal artery (31,32). In contrast, high-salt diets and hyperfusion significantly inhibited nNOS mRNA expression (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In studies concerning the influence of sodium intake on NOS expression, it has been found that sodium deficiency stimulates nNOS expression, as do other conditions that are likely to result in reduced MD [NaCl] or transport, such as furosemide administration and unilateral stenosis of the renal artery (31,32). In contrast, high-salt diets and hyperfusion significantly inhibited nNOS mRNA expression (31,32). But in the other experiments in which the urinary excretions of nitrate and nitrite were measured, Shultz and Tolins (33) found that high salt intake generated more NO in MD cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ni and Vaziri (76) observed a decrease in medullary protein expression of NOS I and II after 3 wk of an 8% sodium diet. Others found no change in medullary mRNA expression of any of the NOS isoforms (98,113).…”
Section: Influence Of Medullary No Production On Blood Pressure Salt mentioning
confidence: 96%